Factors Affecting Neonatal Hearing Screening Follow-up in Developing Countries: One Insitution Prospective Pilot Study - Hrncic, Nermin (Medeni Med J, 2021)
OBJECTIVE: To detect factors related with loss to follow-up (LTF) in neonatal hearing screening (NHS) program of one institution in a developing country. METHODS: A prospective study was planned based on the data collected in a pilot study conducted a year before in the same institution. In this pilot study, hearing screening was performed before hospital discharge for every infant (1217 newborns) in six months period. Total referral rate was 19.1% (223/1217). Loss to follow-up (LTF) was 38.1% (85/223). Telephonic interviews were done with 50 parents who had not come with their child to the second hearing test. For these telephonic interviews the questionnaire with four sections (socio-demographic information; information about pregnancy, birth, and present health condition of the child; caregiver knowledge of neonatal hearing screening, and reasons for default on follow-up) was created. RESULTS: The mothers participated in this study were 29.1 years (±5.2 SD) of age in average. Place of residence was mostly rural (64%; n=32) with 39.4 Km (±24.8 SD) away from from the rescreen referral center. Their knowledge on neonatal hearing screening, hearing impairment incidence or treatment opportunities was at a very low level. Caregivers’ perceptions that follow-up was unnecessary (50%; n=25), was most frequently given reason for follow-up default, followed by newborns bad health condition (12%; n=6) and forgetting about the follow-up visits (8%; n=6). CONCLUSION: The main reason for default in follow-up in our study was caregiver’s poor knowledge about this topic.